Urban cultural amenities and the migration of the creative class. - Dalvai, Wilfried (My University, 2016)
This paper models the migration of the Creative Class (Florida, 2003) in a New-Economic-Geography framework. Beside wage differentials, urban cultural amenities play an important role on the choice of location. A public cultural good, financed by taxes, is introduced as an agglomeration force. The public-good is purely consumed by skilled workers. Additionally urban cultural diversity across cities is taken into account to model exogenous differences between cities. I analyze the political equilibrium of tax competition. Furthermore the effects of asymmetries of cities and trade liberalization is examined. There is an optimal level of provision of public cultural goods. In the dispersion-scenario the equilibrium tax rate for workers is hump-shaped with respect to trade integration while for skilled workers it is u-shaped. In the core-periphery scenario the equilibrium tax rate for the core decreases with increasing trade freeness.
Keywords: Standort; Standortfaktor; Kultur; Wohnstandort; Standortwahl; Stadtökonomie; Wirtschaftsgeographie; Weicher Standortfaktor; Kulturangebot; Kreativwirtschaft; Qualifikation